'Speaking with them, not about them': engaging undergraduate social work students in research with young people. Issue 1 (2nd January 2020) - Heinsch, Milena; Agllias, Kylie; Tickner, Campbell; Wells, Hannah; Cootes, Hannah; Sampson, Dara; Kay-Lambkin, Frances
ABSTRACT: Young people's involvement in social work education has been limited, despite increased awareness of the importance of young voices in professional education programs. Qualitative research methodologies offer mechanisms for including young people's perspectives in social work education, and tools for social workers to better understand and respond to their concerns. This paper presents an Australian case study of engaging undergraduate social work students in research with secondary school students, to enhance their ability to systematically explore and address young people's needs. Social work students' reflections suggest this experience deepened their understandings of the social and relational challenges young people face during the high school years, improved their self-awareness of assumptions they hold about young people, and enhanced their confidence to identify and address young people's needs in a meaningful way. The paper concludes with an evidence informed discussion about the lessons learned from this study, and the possible implications for integrating similar projects into social work courses in the future.